Prevalence and characterization of Leptospira spp. in slaughter animals at abattoirs in Gauteng, South Africa and the zoonotic risk posed to abattoir workers - Adesiyun, Abiodun Adewale (University of Pretoria, 2024)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2020.